Effectiveness of Extracorporeal Shock Wave Therapy on Postural Control and Balance in Children With Unilateral Cerebral Palsy: A Randomized Controlled Trial - Bilek, Furkan; Tekin, Fatih (Sage Publications Inc, 2021)
The aim of this study was to investigate the effects of Extracorporeal Shock Wave Therapy (ESWT) applied to paraspinal muscles on balance and postural control in children with unilateral Cerebral Palsy (CP). A total of 32 children with unilateral CP were included in the study. The children participated in a one-session control to evaluate their reactions to ESWT before randomly assigning them into experimental and control groups. We evaluated children twice: before and after the treatment. We used the Trunk Control Measurement Scale, Trunk Impairment Scale, Pediatric Balance Scale (PBS), and Timed Up and Go (TUG) test in these assessments. Following the pre-test session, we applied Neuro-Developmental Treatment (NDT) programs to both groups at the rate of twice per week for eight weeks; additionally, we applied ESWT only to the experimental group at the rate of twice a week for eight weeks. While there were trends toward increased trunk control skills, PBS scores and TUG test performances from pre- to post-testing in both groups, these improvements were only statistically significant in the experimental group (p < 0.05). We conclude that for children with unilateral CP, ESWT applied to paraspinal muscles has significant additive value when combined with NDT to improve postural control and balance.
Keywords: balance; cerebral palsy; extracorporeal shockwave therapy; paraspinal muscles; postural control; spasticity